2013
DOI: 10.1177/1545968313491005
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating Walking Speed Poststroke With Treadmill-Based Interventions

Abstract: Background In the past several years, several randomized controlled trials (RCTs) have been reported regarding the efficacy of treadmill-based walking-specific rehabilitation programs, either individually (TT) or combined with body weight support (BWSTT), over control group therapies poststroke. No clear consensus exists as to whether treadmill-based interventions are superior in rehabilitating walking speed (WS) poststroke. Objective To review published RCTs examining TT and BWSTT poststroke and describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
(151 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, it may accelerate the development of independent walking in children with Down syndrome (Damiano and DeJong, 2009 ; Valentin-Gudiol et al, 2013 ). Stroke patients who are able to walk, but not those unable to walk, benefit from the intervention by increasing walking speed and endurance (Mehrholz et al, 2014 ), although the superiority of the intervention relative to other control therapies has failed to be established (Charalambous et al, 2013 ). In SCI patients, locomotor training may induce the reappearance of kinematic regularities (Grasso et al, 2004a ), EMG temporal components shared by multiple muscles (Ivanenko et al, 2003 ), and flexor reflexes (Smith et al, 2014 ).…”
Section: Clinical Applications Of Simulated Hypogravitymentioning
confidence: 99%
“…On the other hand, it may accelerate the development of independent walking in children with Down syndrome (Damiano and DeJong, 2009 ; Valentin-Gudiol et al, 2013 ). Stroke patients who are able to walk, but not those unable to walk, benefit from the intervention by increasing walking speed and endurance (Mehrholz et al, 2014 ), although the superiority of the intervention relative to other control therapies has failed to be established (Charalambous et al, 2013 ). In SCI patients, locomotor training may induce the reappearance of kinematic regularities (Grasso et al, 2004a ), EMG temporal components shared by multiple muscles (Ivanenko et al, 2003 ), and flexor reflexes (Smith et al, 2014 ).…”
Section: Clinical Applications Of Simulated Hypogravitymentioning
confidence: 99%
“…To collectively address these factors and to promote greater opportunity for motor learning during gait rehabilitation, several studies recommend treadmill-based gait training paradigms [ 15 ], including the recent American Heart Association (AHA) scientific report for exercise training in stroke survivors [ 16 ]. However, most treadmill paradigms, especially those that integrate limb unweighting via body weight support (BWS), have had varying degrees of success over the past few decades, with some studies reporting no significant outcome differences compared with over-ground training approaches [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 BWSTT has been shown to have superior outcomes regarding gait speed compared to cycle ergometry with or without concomitant strength training in stroke patients. 10 Charalambos et al, 11 concluded that there was no significant difference between BWSTT and other interventions. 11 Veerbeek et al showed significant effect size for use of body weight support treadmill training for improving gait speed.There are several rationales for the use of BWSTT for improving gait function in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…10 Charalambos et al, 11 concluded that there was no significant difference between BWSTT and other interventions. 11 Veerbeek et al showed significant effect size for use of body weight support treadmill training for improving gait speed.There are several rationales for the use of BWSTT for improving gait function in stroke patients. One rationale is the concept of mass practice, where multiple repetitions of a movement drive changes in corticomotor stimulation.…”
Section: Introductionmentioning
confidence: 99%